Intergovernmental Relations Trumps Social Policy Change: Trudeau, Constitutionalism, and Family Allowances - Blake, Raymond (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractFamily allowances were one of the few programs shared by all Canadian families from 1945 to 1992, and one of the few means of building social cohesion across Canada. Family allowances became embroiled in the minefield of Canadian intergovernmental relations and the political crisis created by the growing demands from Quebec for greater autonomy from the federal government in the early 1970s. Ottawa initially dismissed Quebec’s demands for control over social programs generally and family allowance in particular. However, Prime Minister Pierre Trudeau offered family allowance reforms as a means of enticing Quebec Premier Robert Bourassa to amend the British North America Act. The government’s priority was constitutional reform, and it used social policy as a bargaining chip to achieve its policy objectives in that area. This study shows that public policy decisions made with regard to the family allowance program were not motivated by the pressing desire to make more effective policies for children and families.